Developing Students’ Book Characterized Realistic Mathematics Education (RME) to Improve Numeration Literacy Skill - Aini, Khafidhoh Nurul; Asmana, Arezqi Tunggal; Rosyid, Halimur (JURNAL EKSAKTA PENDIDIKAN (JEP), 2024)
The purpose of this research was to develop a Student Book with Realistic Mathematics Education (RME) characteristics in terms of the results of validity, practicality, and effectiveness tests. The development of this student book uses the Plomp model that was carried out in three phases, namely: (1) Preliminary research, (2) Prototyping phase, and (3) Assessment phase. In the Preliminary research phase, it was found that the numeracy literacy skills at State Elementary School 2 Padenganploso were still low and the teaching materials used did not contain problems in everyday life that were relevant to the environmental conditions around students. In the Prototyping phase, student book development was carried out using steps that follow the principles and characteristics of RME. In the Assessment phase, based on the results of expert validation, an average score of 3.86 was obtained for all aspects, which means that the RME student book can be stated to be valid. From the observations of the implementation of the student book, a score of 3.87 is obtained, which means that the practical test by the observer meets the Practical criteria. From working on the numeracy literacy questions, it was found that 90% of students scored above 65, and the results of the N-Gain calculation as a whole obtained an average score of 0.71 with a high interpretation. The results of observations of student activity obtained an average of 3.8 with the active category, and the results of student responses obtained 90% gave a positive response, which means that the student book with RME characteristics meets the criteria of Effectiveness.